CPS Women's research and action forum - O'Keefe, Jennifer (2017)
« The Changing Public Services (CPS) project’s Atlantic Cluster, based primarily in Halifax, Nova Scotia, concluded its research in the fall of 2016. To summarize their findings and to report back to the community, the cluster hosted a public event called the “Women’s Research and Action Forum”. The event brought together feminist academics, advocates, members of labour unions, students and others to not only learn about research results but to engage with it in an interesting and meaningful way. This paper summarizes and reflects on the events of the Forum » [Résumé original]
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; canada; forum; groupes de femmes; nouvelle-écosse; orpcc; outils; pour des recherches en milieux de pratiques; périodes historiques; recherche en milieux de pratique; ressource en ligne; régions géographiques